Comparative analysis of the specific motor skills of cadets by classes after the second year of education - Marić, Lela D.; Ranđelović, Mile P. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Despite the era of digitization, the assessment of the combat readiness of modern army members has always been associated with good physical fitness. When it comes to the specific physical abilities of the Military Academy cadets, their previous tests indicate that the values are within the expected limits. The aim of this work is to compare the values of the results in the specific motor skills of cadets by classes (groups) after the second year of schooling. It is hypothesized that there are differences in the results of the cadets by groups.Methods: The sample consisted of a total of 932 male cadets within nine groups, after the second year of study, starting from the 2012/2013 school year. Four variables related to specific motor skills were included: pull-ups on a bar for 2 minutes, crunches for 2 minutes, 3200 m running, and overcoming infantry obstacles. Using statistical programs, the results of these four variables were processed through central and dispersion parameters. The univariate analysis of variance (ANOVA) was used to determine the differences between the groups in the achieved results. The multivariate analysis of variance (MANOVA) determined the differences in the system of variables with spaces.Results: The analysis of the results of the specific motor abilities by groups after the second year of study determined that there are statistically significant differences in the variables “pull-ups on a bar” and “crunches”, while there are no statistically significant differences in the variables “3200 m running” and “overcoming infantry obstacles”.Conclusions: The values of the results of the cadets in these four specific motor abilities are obviously within the limits provided by the Instructions and standards for evaluating cadets by age, so it was determined that there are no greater deviations than expected.
Keywords: ANOVA; MANOVA; combat readiness; motor skills; pull-ups; crunches; infantry obstacles